Body composition variables as predictors of NAFLD by ultrasound in obese children and adolescents - Monteiro, Paula Alves [UNESP]; Mello Antunes, Barbara de Moura [UNESP]; Silveira, Loreana Sanches [UNESP]; Destro Christofaro, Diego Giulliano; Fernandes, Romulo Araujo; Freitas Junior, Ismael Forte (Biomed Central Ltd., 2014)
Background: Nonalcoholic fatty liver disease (NAFLD) is a disorder associated with excessive fat accumulation, mainly in the intra-abdominal region. A simple technique to estimate abdominal fat in this region could be useful to assess the presence of NAFLD, in obese subjects who are more vulnerable to this disease. The aim of this cross-sectional study was to verify the reliability of waist circumference and body composition variables to identify the occurrence of NAFLD in obese children and adolescents.Methods: Sample was composed of 145 subjects, aged 11 to 17 years. Assessments of waist circumference (WC), trunk fat mass (TFM) and fat mass (FM) by dual-energy X-ray absorptiometry (DXA) and ultrasound for diagnosis of NAFLD and intra-abdominal adipose tissue (IAAT) were used. Correlation between variables was made by Spearman's coefficients; ROC curve parameters (sensitivity, specificity, area under curve) were used to assess the reliability of body composition variables to assess the presence of NAFLD. Statistical significance was set at 5%.Results: Significant correlations were observed between NAFLD and WC (p = 0.001), TFM (p = 0.002) and IAAT (p = 0.001). The higher values of area under the ROC curve were for WC (AUC = 0.720), TFM (AUC = 0.661) and IAAT (AUC = 0.741).Conclusions: Our findings indicated that TFM, IAAT and WC present high potential to identify NAFLD in obese children and adolescents.
Keywords: Body composition; Obesity; Fatty liver; Children; Adolescents